Greenhouse untuk Meningkatkan Ketahanan Pangan Lokal dalam Menghadapi Perubahan Iklim di Desa Tellumpanua Kecamatan Tanete Rilau Kabupaten Barru - Rais, Rahmi; Aidah, Aidah; Nurlia, Nurlia (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to enhance local food security through the construction and utilization of a greenhouse in Tellumpanua Village, Tanete Rilau District, Barru Regency, as an adaptation measure to the impacts of climate change. The greenhouse serves as a horticultural production facility capable of controlling temperature, humidity, and light intensity, enabling crops to grow optimally throughout the year. The activities were carried out through several stages, including planning, facility construction, management training for farmer groups, and assistance during the cultivation process. The results indicate that the use of greenhouses can increase productivity and crop quality while reducing the risk of crop failure due to extreme weather. Collaboration among universities, farmers, and the village government was identified as a key factor contributing to the program’s success. The application of greenhouse technology is expected to be replicated in other areas as a sustainable agricultural adaptation strategy to climate change.